“Design and Development of Geographic Information Systems in Desa Mekar Buana, Kecamatan Tegalwaru, Kabupaten Karawang Web-Based” - Simorangkir, Holder; Aji Mabroery, Andika; Erzed nixon, Nixon; Fauzi, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to create a Tourism Geographic Information System to expose tourism information in Desa Mekar Buana, Kecamatan Tegalwaru, Kabupaten Karawang to the wider community. This GIS is useful for people who need information on tourist attractions to help and is also useful as a design analysis media in the process of building facilities and infrastructure in Desa Mekar Buana. Desa Mekar Buana has a large area of 18.63 km². Desa Mekar Buana has coffee plantations, bananas, durian, mangosteen with an overall plantation area of 6.01 km². This village also has tourist attractions that are not less interesting than other tourist attractions. Tourism in Desa Mekar Buana consists of natural attractions namely Bandung waterfalls, Cigentis waterfalls and Gunung Sanggabuana. Artificial tourism, namely the bridge of love and fishing Tuana Tirta. Desa Mekar Buana also has a culinary tour and an inn called a tourist village, because this village was chosen to be the Desa EMAS which means Entrepreneur, Mandiri, Adil and Sejahtera. Kabupaten Karawang from 20 selected villages in West Java to use the pilot village. In this research the analysis method used is the SWOT method and the system builds up using a prototype method. The programming language used is JavaScript. The database used is MySQL and the tools used are XAMPP, Note C ++, Adobe Dreamweaver. The results of this study are designing a web GIS that can help increase tourism visitors for the welfare of the people of Desa Mekar Buana.